Performance of different crops productivity enhancement through adaptation of crop varieties at charland in Bangladesh - Islam, MN; Rahman, MS; Alom, MS; Akhteruzzaman, M (Bangladesh Journal of Agricultural Research, 2016)
Charland that are emerged as islands within the river channel or as attached land to the riverbanks as a result of erosion and accretion. In crop production systems, screening of adaptable crop varieties for charland is necessary to address the climate change issues. Hence, five separate experiments were conducted at charland of the Padma River in Kushtia district during November 2012 to May 2013 to select suitable varieties of lentil, hybrid maize, soybean, potato and mustard for increasing crop productivity. The experiment comprised of four lentil varieties viz. BARI Masur-4, BARI Masur-5, BARI Masur-6 and a local cultivar; four hybrid maize varieties namely BARI Hybrid maize-5, BARI Hybrid maize-7, BARI Hybrid maize-9 and Pacific-11; three soybean varieties like BARI Soybean-5, BARI Soybean-6 and Shohag; four potato varieties viz., BARI Alu-7, BARI Alu-8, BARI Alu-31 and Belgium; and five mustard varieties viz., BARI Sarisha-11, BARI Sarisha-13, BARI Sarisha-14, BARI Sarisha-15 and BARI Sarisha-16 were evaluated separately in five trials for their adaptation in charland. Among the studied crops, lentil var. BARI Masur-6, maize var. BARI Hybrid maize-9, soybean var. BARI Soybean-6, potato var. BARI Alu-7 and mustard var. BARI Sarisha-11performed better in the charland under climate change situation in Bangladesh. Bangladesh J. Agril. Res. 40(4): 629-640, December 2015